If only I knew: Nutrition behavior change delivered by women's groups has impacts on diet quality that are mediated by knowledge in rural Bihar, India - Raghunathan, Kalyani; Menon, Purnima; Kumar, Neha; Gupta, Shivani; Chauhan, Tarana; Pandey, Shinjini; Kathuria, Ashi (American Society for Nutrition, 2020)
Poor diets are a major challenge in India. Barriers to improving diets include limited knowledge, access to resources and availability of affordable nutritious foods. Bihar, a poor state in India, has scaled up women's savings and credit self-help group (SHG) programs state-wide to improve livelihoods and access to resources. SHGs are now being leveraged to integrate health and nutrition discussions into their activities but rigorous evidence on the impact of integration is limited.